TRANSFER OF LOADS FROM THREE HETEROGENEOUS ELASTIC STRINGERS TO AN INFINITE SHEET THROUGH ADHESIVE LAYERS - Kerobyan, Aghasi V.; Sahakyan, Karen P. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2023)
This paper considers the problem for an elastic infinite plate (sheet), which on parallel finite parts of its upper surface is strengthened by three finite stringers, two of which are located on the same line, having different elastic properties. The stringers are deformed under the action of horizontal forces. The interaction between infinite sheet and stringers takes place through thin elastic adhesive layers having other physical-mechanical properties and geometric configuration. The problem of determining unknown shear stresses acting between the infinite sheet and stringers is reduced to a system of Fredholm integral equations of second kind with respect to unknown functions, which are specified on three finite intervals. It is shown that in the certain domain of the change of the characteristic parameters of the problem this system of integral equations can be solved by the method of successive approximations. Particular cases are considered, the character and behaviour of unknown shear stresses are investigated. Further, for various values of changing characteristic parameters of the problem the multiple numerical results and its analysis are presented.
Keywords: elastic infinite plate; infinite sheet; parallel elastic stringers; contact; adhesive layer; system of integral equations; operator equation